Training through gametherapy promotes coactivation of the pelvic floor and abdominal muscles in young women, nulliparous and continents - Silva,Valeria Regina (2016)
ABSTRACT Introduction and objectives: Several studies have been investigated co-activation can enhance the effectveness of PFM training protocols allowing preventive and therapeutic goals in pelvic floor dysfunctions. The objective of the present study was to investigate if an abdominal-pelvic protocol of training (APT) using gametherapy would allow co-activation of PFM and transversus abdominis/oblique internal (TrA/OI) muscles. Patients and methods: Twenty-five nulliparous, continent, young females, with median age 24.76 (±3.76) years were evaluated using digital palpation (DP) of PFM and surface electromyography of PFM and TrA/OI simultaneously, during maximal voluntary contraction (MVC), alternating PFM and TrA/OI contraction requests. All women participated on a supervised program of APT using gametherapy, that included exercises of pelvic mobilization associated to contraction of TrA/OI muscles oriented by virtual games, for 30 minutes, three times a week, in a total of 10 sessions. Electromyographic data were processed and analyzed by ANOVA - analysis of variance. Results: When MVC of TrA/OI was solicited, it was observed simultaneous increase of electromyographic activity of PFM (p=0.001) following ATP. However, EMG activity did not change significantly during MVC of PFM. Conclusion: Training using gametherapy allowed better co-activation of pelvic floor muscles in response to contraction of TrA, in young nulliparous and continent women.